ADAPTASI RUMAH TANGGA NELAYAN PULAU HARUKU TERHADAP DAMPAK PERUBAHAN IKLIM (STUDI KASUS DI NEGERI HULALIU DAN ABORU) - Ruban, Angela; Wattimury, Margie (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
The dependence of fisher households on fisheries resources is highly affected by climate change, therefore fishermen must be adaptive to all changes. Adaptation to climate change generally varies according to the potential owned and the ability of fishermen and the government. This study aims to determine the adaptation activities carried out by fishermen households in Negeri Hulaliu and Negeri Aboru of Central Maluku Regency due to climate change in the economic aspect. Primary data was obtained from interviews with 17 fishing households of Hulaliu Village and 14 fishing households of Aboru Village. Secondary data were obtained from various related agencies and scientific literature related to this research. Data analysis was conducted using descriptive qualitative analysis to determine the types of adaptation activities carried out and quantitative analysis to analyse the amount of income earned. The results showed that adaptation efforts to climate change made by fishermen to continue to earn income when they cannot carry out fishing activities are by utilising agricultural potential. entrepreneurship and cattle. Income from fishing is known in Hulaliu Village at IDR 5.333.733/month and Aboru Village at IDR 4.454.466/month, while income from farming is IDR 925.000/month, entrepreneurship is IDR 500.000/month, and farming is IDR 800.000/month in Hulaliu Village, in Aboru Village it is known that farming is IDR 1.100.000/month, entrepreneurship is IDR 700.000/month, and farming is IDR 200.000/month.